Analisis Pengaruh Inflasi, Suku Bunga dan NPF Terhadap Profitabilitas ROA Bank Umum Syariah Di Indonesia - Vindi Indah Sari (JURNAL EKOBIS DEWANTARA, 2021)
The purpose of this study is to find out if inflation, interest rates and NPF (Non Performing Finance) have a significant impact on ROA on sharia banks in Indonesia period 2014-2018, both partially and simultaneously. The population in this research is the sharia Bank in Indonesia, registered with OJK (Kuangan Service Authority). The period of observation used was 2014-2018 or for 5 years. The sample used is by using the Purposiv sampling method, so that a sample of 13 research samples was obtained at times of the observation period over 5 years into 65 research data. The technical analysis of data used is a method of double linear analysis with a significant rate of 5% (0.05). The results of this study showed that inflation has no significant negative influence on ROA. Interest rate variables have no significant negative impact on ROA. While NPF (Non Performing Finance) variables have significant negative effect on ROA. The ability of independent variables describes ROA's dependent relationship of 51,% while the rest of its 48.2% in the influence of other factors not examined in this study.